A snapshot of circulation failure following acute traumatic injury: The expansion of computed tomography beyond injury diagnosis. Issue 1 (January 2016) - Anand, Tanya; vanSonnenberg, Eric; Gadani, Kiran; Skinner, Ruby
Abstract: Objective: CT scans with a flat Inferior Vena Cava (IVC) suggest hypovolemia, and the presence of shock bowel implies hypoperfusion. The purpose of this study is to correlate injury severity, resuscitation needs, and clinical outcomes with CT indices of hypovolemia and hypoperfusion. Design: Retrospective cohort study. Setting: Level II trauma centre in Central California. Patients: Adult patients imaged with abdominal and pelvic CT scans, from January 2010–January 2011. Interventions: None. Measurements and main results: Circulatory derangements on CT scans were defined as an IVC (AP) diameter measurement of <9 mm, flat IVC (FIVC), hypovolemia. The presence of small intestine hypoperfusion was shock bowel (SB). The absence of these findings was a normal CT scan (NCT). Comparisons of acid-base status, fluids, morbidity and mortality were made based on CT findings. Subgroups were: FIVC ( n = 20), FIVC + SB ( n = 19), SB ( n = 4) only versus normal CT scans, NCT ( n = 47). Results: Overall ISS was 19 (SD) 14. The lowest ISS was in NCT 14 (SD) 10 and there was an incremental increase in ISS based on circulatory derangements, p = 0.001. ICU admission was lowest in NCT and highest in the presence of hyovolemia and hypoperfusion, p = 0.03. Similarly ED crystalloid requirements and the activation of a massive transfusion protocol (MTP), was lowest in NCT group and gradually increased significantly as hypovolemia and hypoperfusion was demonstrated on CT scans. Additional parameters such as metabolic acidosis, nosocomial infections and mortality were associated with acute CT findings of circulatory failure. Conclusions: Hypovolemia and hypoperfusion, markers of abnormal circulation, were demonstrated on CT scans for trauma evaluation. The presence of these findings alone or in combination showed strong correlation with high injury severity, and the need for aggressive resuscitation.